Automatic lineaments mapping and extraction in relationship to natural hydrocarbon seepage in Ugwueme, South-Eastern Nigeria - Enoh, Mfoniso Asuquo; Okeke, Francis Ifeanyi; Okeke, Uzoma Chinenye (Geodesy and Cartography, 2021)
The study focus on the integration of Remote Sensing and Geographic Information System for identification and delineation of lineaments in relation to natural hydrocarbon seepage, which occur in Ugwueme, South-Eastern Nigeria. To achieve this objective, remotely sensed data (ASTER Digital Elevation Model and Landsat 8 OLI/TIRS) were used to depict the surface expression of faults, folds and fractures which are expressed in the form of lineaments.  The global positioning system (GPS) was also used for ground verification. The geology map of the study area, which is elucidated in the geology of Nigeria was used to show the distribution of rocks and other geologic structures. The delineation of lineament features was done automatically with the PCI Geomatica while the Rock ware was used to generate the Rose diagram for demonstration of the direction of the extracted lineaments. The classification of the lineaments density and the lineaments intersection analysis were categorized as very low, low, moderate, high and very high classes respectively. Areas classified as very high to high lineaments density are potential zone, which act as conduits for hydrocarbon seepage. The result shows that a total lineament frequency of 947 km and a total lineament length of 946 km were delineated from the satellite data. The result further shows that areas with high lineaments density are concentrated in the southwest, south, central and northern part of the study area while areas with low lineament density were found within the eastern part of Ugwueme. The Rose diagram highlight the major trend in the (NE-SW), (N-S) and (NW-SE) directions, and the minor trend in the (W-E) direction.  These directional trends depict the directions of lineaments which act as conduits zones for hydrocarbon seepage in the region.  The overall findings of the study shows that lineament density, lineament intersection and rose diagrams are concepts applicable in hydrocarbon oil and gas seepages.